Contributions to think about the relationships established between documentary filmmakers and leader folkcommunicators (Revista Internacional de Folkcomunicação, 2021)
The work studies the relationships established between documentary filmmakers and leaderfolkcommunicators, identifying if the represented relationships are the result of a dialogicalethics, in the light of the buberian philosophy and folkcommunication. The research seeks toreflect on the relationships between those who produce documentaries and those who arefilmed, due to the fact that the Brazilian media represents, in a generalist way, the peripheralfemale and male subjects. As a methodology, the work makes use of bibliographic researchand descriptive film analysis on the Brazilian documentaries Fala Tu (2003) and Aqui Favela: orap representa (2003). The choice of films is due to the difference in the approach about thehip hoppers and for the proximity in the realization of the productions. Thus, this work soughtto reflect, specifically, about the relationships (ethi cs, non-ethics) that can be identified indocumentary film productions, however, the notes fit for other media that promise assertionsabout the historical world.